AgroMax : Development of Low-Cost, Android-Controlled Spraying Robot Towards Smart Agriculture - Shivam Khairnar; Ishwari Nikam; Anushka Biaragi; Shinde Sanika; Amol P Vadnere (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Pesticide and herbicide applications play a critical role in safeguarding crops from pests and diseases. However, conventional manual spraying techniques are often inefficient, labor-intensive, and pose serious health risks to farmers due to prolonged exposure to harmful chemicals. These methods also tend to result in uneven chemical distribution and excessive usage, contributing to environmental concerns. Moreover, conventional approaches struggle to effectively target pests hidden beneath foliage, leading to suboptimal pest control. In response to these challenges, this research presents the design and development of an autonomous agricultural spraying robot aimed at enhancing precision, safety, and sustainability in modern farming. The system is equipped with sensors, a live-feed camera, and automated spraying nozzles, enabling real-time monitoring and targeted application of pesticides. This approach minimizes chemical wastage, reduces environmental impact, and enhances the effectiveness of pest management. By automating the spraying process, the robot also limits human exposure to hazardous substances, creating a safer working environment for agricultural workers. Additionally, the robot is powered by a rechargeable battery, making it an eco-friendly solution suitable for repetitive field operations. Designed for versatility, it can adapt to various crops and farm layouts, offering functions beyond spraying, such as grass cutting. This study demonstrates the potential of robotic automation in transforming conventional agricultural practices by providing a cost-effective, scalable, and sustainable solution. The proposed system contributes to increased productivity, and improved pest control, and supports the transition toward more environmentally responsible farming methods.